Analisis Butir Soal IPA Try Out USBN Tahun Ajaran 2018/2019 dalam Kaitannya dengan Level Kognitif - Huda, Nuril; Wahyuni, Tutik Sri (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2019)
This research aims to: 1) find out the characteristics of the science items try out National Standar School Exams (USBN) in the academic year 2018/2019 based on Classical Test Theory (CTT); 2) find out the number of the science items try out USBN in the academic year 2018/2019 in relation to cognitive level. This type of research is a descriptive research with a quantitative approach. The data obtained was a computer answer sheet of 5022 students who took USBN try out of Elementary School 2019 on February 21, 2019 in Tulungagung Regency. The results showed that: 1) The characteristics of the science items try out USBN in the academic year 2018/2019 based on Classical Test Theory (CTT) in aspects of: a) validity of 35 items valid; b) the reliability value of 0.818 is very high; c) the level of difficulty level: 4 items (11.43%) are difficult, 9 items (25.71%) are moderate, 16 items (45.71%) are easy and 6 items (7.140%) are very easy; d) discriminating power: 3 items (8.57%) are bad, 12 items (34.29%) are good enough, 15 items (42.86%) are moderate, and 5 items (14.29%) are good; e) the quality of options: 17 items (48.57%) without revision, 9 items (25.71%) one option revision, 5 items (14.29%) 2 option revisions, and 4 items (11.43% ) wrong revision of 3 options; f) 13 items (37.14%) about the science try out USBN in the academic year 2018/2019 have quite good and good characteristics, so they can be included in the question bank; 2) items the science of Â try out USBN in the academic year 2018/2019 in relationship with cognitive level, 11 items (31.43%) category L1 (knowledge), 10 items (28.57%) category L1 (understanding), 4 items (11.43%) category L2 (application), and 10 items (28.57%) category L3 (reasoning). Of the 13 items entered in the question bank with cognitive level, the science try out USBN in the academic year 2018/2019 was dominated at the cognitive level L1 (knowledge and understanding).